Urban Green Equity: Overview of Scientific Research from 1992 to 2021 - Maira Muniz Almeida, Wanda; Guaraldo, Eliane (Journal of Interdisciplinary Lifestyle Studies, 2022)
The growing concern with the impacts of climate change and the fast urbanization of cities has led international policies to guide changes in attitudes by governments and civil society, directing effective models of sustainable governance aimed at environmental health and equal access for society environmental benefits. In this study, we seek to understand the evolution of research and scientific production on a topic of great relevance today – green equity. Through scientometric analysis based on a systematic literature review, we analyzed articles published in the period between 1992 and 2021. We used the open source R-tool Biblioshiny, which processes information from academic databases to carry out the analyses. Through this methodology it was possible to identify the main fields of research and relate the results obtained with important historical milestones for sustainable development. We also seek to highlight the evolution of research lines and highlight the significant flows in the global collaboration network. We found that the theme of green equity was driven by international agendas such as the SDG and has been gaining more space in scientific production, linked to a greater variety of issues such as climate change, accessibility to green spaces, ecosystem services, green infrastructure and socioeconomic issues.